Some Thoughts on the Administration of the Regional Development in the Member States of the EU – In the Light of the Role of the Municipal Bodies - István Hoffman (Central European Public Administration Review)
Municipalities are traditionally responsible for several regional planning and development tasks even if different systems have evolved in the Member States of the European Union. The administration of regional planning has been strongly influenced by the European integration. The allocation of the European Structural and Investment Funds was a major task of the recipients. The regional approach of the structural funds was a catalyst for the territorial reforms in several EU Member States. Although originally the regional reforms were based on the NPM-related reforms the changes were supported by the post-NPM paradigms (especially by the Good Governance paradigm) as well. In several countries the Crisis caused centralisation and the concentration of the structures. Thus three major models could be distinguished: centralised regional development systems, decentralised systems and federal systems. The characteristics of these systems are reviewed in the article focusing on their major differences and similarities.